The Influence Of The Role Of The Family On The Prevention Of Repeated Stroke In Medan Tuntungan Year 2020 - Aspiati Aspiati; Roy Wilson Sihaloho (Sean Institute, 2021)
Cases of stroke in Indonesia continue to soar, in 2016 the results of research in several areas of Medan Tuntungan found 23,636 sufferers due to stroke and will continue to increase in 2020 as many as 500,000 Indonesians have had strokes and around 125,000 of them have died or been disabled for life. This type of research is cross sectional. The research was conducted in the Medan Tuntungan Region in 2020. The research was conducted in April - July 2020. The study population was all families of recurrent stroke patients in the Medan Tuntungan Region. The sample is a family of stroke sufferers, the research sample was taken by purposive sampling. The number of samples is 34 people. The data collection method taken is primary data. Data analysis was cross sectional, namely knowing the role of the family in efforts to prevent recurrent stroke, data processing was done by editing to check or ensure that the questionnaire sheet had been filled in properly. Then proceed with coding, namely by giving certain codes or numbers on the questionnaire sheet to facilitate data analysis. The results showed that the influence of the role of the respondent's family in preventing recurrent stroke was 5 people (14.7%) who did not give enough role, 21 people (61.8%) who gave enough family role, 8 people (23.5%) who gave a good family role.